ARTIKEL REVIEW :KANDUNGAN EKSTRAK ETANOL DAUN SIRIH (Piper Betle L) SEBAGAI ANTIOKSIDAN - Restu Hidayanti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Betel leaf (Piper betle L.) is an Indonesian medicinal plant rich in secondary metabolites with strong natural antioxidant potential. This literature review aimed to analyze the antioxidant activity of major bioactive compounds in betel leaf and to identify the most potent constituents. Relevant articles were collected from PubMed, Google Scholar, and Science Direct using the keywords Piper betle and “antioxidant activity,” focusing on studies employing the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Antioxidant activity was expressed as IC₅₀, the concentration required to scavenge 50 % of free radicals. Results demonstrated an inverse relationship between IC₅₀ and antioxidant strength. Compounds with very strong activity included eugenol (18.27 µg/mL), hydroxychavicol (22.50 µg/mL), and total phenolics (21.48 µg/mL). Total flavonoids (35.20 µg/mL) and tannins (42.76 µg/mL) showed strong activity, whereas saponins (53.10 µg/mL) and alkaloids (60.25 µg/mL) were moderate. These findings highlight phenolic constituents—particularly eugenol and hydroxychavicol—as the main contributors to the antioxidant potential of Piper betle ethanol extract and support its use as a natural antioxidant source